An alternative approach to student assessment for engineering–laboratory learning. Issue 2 (3rd July 2017) - Lal, Sulakshana; Lucey, Anthony D.; Lindsay, Euan D.; Sarukkalige, Priyantha R.; Mocerino, Mauro; Treagust, David F.; Zadnik, Marjan G.
Abstract: Assessment of students' performance in laboratory activities evaluates students' achievements and weaknesses in practical work. This is vital from both student and institutional perspectives. Practical skills assessment methods evaluate students on three major components: the ability to collect data and perform calculations, to analyse the cause of failures in the process, and finally students' active engagement and participation in the practical work. A conventional, report-based, assessment method combined with an alternative method, termed in-class assessment, were developed and used for second-year Fluid Mechanics laboratory work. In this article, we describe these two approaches and present the results of a quantitative investigation of students' responses. Students expressed similar experience and satisfaction levels for each of the assessment methods that measured the attainment of different but essential personal and professional skills stipulated by the professional body for students graduating with an engineering degree. These skills include the development of research skills, conceptual understanding, application of techniques, preparing a report, team working abilities and the communication skills needed to interact with peers and demonstrators effectively. This article shows that the use of in-class assessment can serve as a useful complement to conventional report-based assessment methods ensuring optimal laboratory learning for students across engineering knowledge and skills areas.